Impact of ebb-delta dynamics on shoreline evolution along inlet-interrupted coasts - Bamunawala, Janaka; Ranasinghe, Roshanka; Sirisena, Jeewanthi (Frontiers in Marine Science, 2023)
Shorelines adjacent to tidal inlets are highly dynamic landforms affected by oceanic (e.g., sea-level rise) and terrestrial (e.g., fluvial sediment supply) processes. Climate change is thus expected to have substantial physical impacts on these inlet-interrupted coasts. Numerical simulation of such impacts requires a holistic approach where at least the major governing processes that affect the local sediment budget are considered. The Generalized-Scale-aggregated Model for Inlet-interrupted Coasts (i.e., G-SMIC) is such a model that is capable of holistically simulating the evolution of inlet-interrupted coasts over multi-decadal to century time periods. However, in its present form, G-SMIC does not consider the effects of ebb-delta dynamics in its computations. Here, we improve the model to include ebb-delta dynamics and pilot the improved model (G-SMIC+) at two selected case study sites in Vietnam (Thu Bon estuary) and Wales, United Kingdom (Mawddach estuary). Model hindcasts of G-SMIC+ at both case study locations show reasonable agreement with available records of shoreline variations. The evolution of the two inlet-estuary systems was assessed over the 21st century under four of the IPCC’s sixth assessment report climate scenarios (viz., SSP1-2.6, SSP2-4.5, SSP3-7.0, and SSP5-8.5). Results show that both systems switch between sediment exporting and sediment importing systems over the study period (2031 - 2100). Moreover, while the inclusion of ebb-delta dynamics may decrease the erosion volumes of the up-drift shoreline by up to 37% and 46% at Thu Bon and Mawddach estuaries, respectively (by 2100, relative to 2030), the down-drift coast is only affected in a noticeable way at the Mawddach estuary, where the accretion volume is projected to reduce by 50%. As a result, the ebb-delta effect decreases the up-drift shoreline retreat by up to 37% and 48% at Thu Bon and Mawddach estuaries, respectively, while it reduces shoreline progradation of the down-drift coast of Mawddach estuary by up to 50%. These results highlight the importance of including ebb-delta dynamics in modelling efforts to assess the climate change responses of inlet-interrupted coasts worldwide.